2018
DOI: 10.1371/journal.pone.0189847
|View full text |Cite
|
Sign up to set email alerts
|

Can simple trachelectomy or conization show comparable survival rate compared with radical trachelectomy in IA1 cervical cancer patients with lymphovascular space invasion who wish to save fertility? A systematic review and guideline recommendation

Abstract: ObjectiveThis study aims to analyze the published literatures on the effect of less radical fertility-preserving procedures, such as conization or simple trachelectomy, on oncological outcomes in IA1 cervical cancer patients with lymphovascular space invasion (LVSI) through a systematic-review.MethodsThe EMBASE and MEDLINE databases and Cochrane Library were searched for published studies reporting the oncological outcomes of conization/simple trachelectomy in these patients, through April 2017. The endpoints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…In our study, although the number of patients is less, nine of sixteen women intended to get pregnant (56.2%) and all 9 of them (100%) were able to conceive. There were 4 miscarriages (28.6%), which is in a similar range as described in recent literature [20,23,24]. Despite the rate of spontaneous conceptions was high (71.4%) in our study, 4 patients needed assisted reproductive technology (ART).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, although the number of patients is less, nine of sixteen women intended to get pregnant (56.2%) and all 9 of them (100%) were able to conceive. There were 4 miscarriages (28.6%), which is in a similar range as described in recent literature [20,23,24]. Despite the rate of spontaneous conceptions was high (71.4%) in our study, 4 patients needed assisted reproductive technology (ART).…”
Section: Discussionsupporting
confidence: 87%
“…This methodical problem was also shown by Shim et al in a recent systematic review. They demonstrate the problem of analysing recurrence and pregnancy rates in early stage cervical cancer (IA1) with lymphovascular involvement treated by LC or SVT, since most studies were retrospective and of small, nonrandomized numbers [ 24 ]. In this respect, our results may contribute additional clinical data to further evaluate LC as a surgical technique that supports fertility preservation with less cervical trauma but with uncompromised oncological safety.…”
Section: Discussionmentioning
confidence: 99%
“…Hartmann et al reported a 7.3% recurrence rate in 41 IA1 patients treated with conization [ 20 ]. However, Shim et al reported that there was no recurrence in a total of 93 patients who underwent conization or simple trachelectomy [ 21 ]. In our series, there was no invasive cancer recurrence in any of the stage IA1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…It includes removal of the uterine cervix and vaginal cuff, and parametrial resection, followed by the creation of an isthmic vaginal anastomosis. 9 The current National Comprehensive Cancer Network (NCCN) recommendation for fertility-sparing trachelectomy is Stage IB1 tumour. 10 Tumour size of less than 2 cm is also included as eligibility criteria for fertility-sparing management of cervical cancer, along with histology (squamous cell carcinoma (SCC), adenocarcinoma and adenosquamous carcinoma), tumour-to-internal os distance of more than 1 cm, cervical stromal invasion less than 50%, lack of parametrial invasion, and lack of LN metastasis (Figure 2).…”
Section: Tumour Size Measurementsmentioning
confidence: 99%